Combatting Domestic Minor Sex Trafficking: An Evaluation of the My Life, My Choice Program in Kentucky - Dyer, Chelsea M. (2018)
A thesis presented to the faculty of the Caudill College of Arts, Humanities, and Social Sciences at Morehead State University in partial fulfillment of the requirements for the degree of Master of Arts by Chelsea M. Dyer on July 11, 2018